The Effect of Using Computerized Financial Statement Analysis on the Efficiency of Financial Performance: An Empirical Case on Industrial Factor in Project Scheduling-Jordan Case Study. (10th November 2022) - Alhosban, Atallah; Al-Habashneh, Fedel; Shawaqfeh, George; Al-Tarawneh, Essa
Abstract : The study aimed to show the of the analysis of financial statements on the efficiency of the financial performance of the industrial sector, whose companies are listed in the financial market in Jordan. The study relied on the analysis of the financial statements for the years 2016–2021 published in the financial market for the industrial sector, and the mediating element was the Corona delinquents. The study relied on the indicators of return on assets, debt ratio, value, and the equation of market value to book value. Among the most important results of the study, several industrial enterprises lacked financial data for the research years, so they were removed from the analysis. The descriptive process test revealed: in the years after and during the Corona pandemic, industrial enterprises' total assets climbed by 12%. Variable net income after tax has increased by 55% in postcoronavirus years in Jordanian industrial public shareholding firms, and this is reflected positively in the shift in profits. The book value of the share for Jordanian industrial public shareholding companies remains stable. The Corona pandemic problem increases asset value and net profit for industrial public shareholding enterprises. Among its most important recommendations are the necessity of having disclosure laws for unusual items, such as the Corona pandemic, and the need for industrial companies to show the impact of the Corona pandemic by announcing their financial statements.